STRATEGI PENGEMBANGAN LEMBAGA PENDIDIKAN PESANTREN BERBASIS MANAJEMEN STRATEGIK MODERN - Moch. Mahdiyan Nasikhin; Muhammadun; Alga Yolanda (Eduvis : Jurnal Manajemen Pendidikan Islam, 2022)
Pesantren educational institutions as indigenous Indonesian educational entities are currently facing multidimensional pressures of change, encompassing technological transformation, shifts in labor market needs, national accreditation demands, and increasingly high community expectations toward graduate quality. Amid such dynamics, many pesantren still rely on traditional management patterns without the adoption of adequate strategic management instruments, thereby potentially losing relevance and competitiveness. This study aims to identify, analyze, and formulate development strategies for pesantren educational institutions that synergistically integrate modern strategic management principles without abandoning the pesantren's value-based identity. The method employed is qualitative with a phenomenological approach through observation, in-depth interviews, and documentation studies at several selected pesantren that are considered to have implemented elements of strategic management. Data analysis was conducted using source and technique triangulation. The findings indicate that effective pesantren development strategies encompass four main pillars, namely: strategic planning based on contextual SWOT analysis, value-based human resource capacity development, diversification of educational programs that are adaptive to industry needs, and strengthening of a quality management system rooted in pesantren culture. The resulting model is expected to serve as an operational guide for pesantren administrators in facing the challenges of the educational globalization era.